The Effects of Negativity and Motivated Information Processing During a Political Campaign - Meffert, Michael F.; Chung, Sungeun; Joiner, Amber J.; Waks, Leah; Garst, Jennifer (Journal of communication, 2006)
This research investigated how voters select, process, are affected by, and recall political information in a dynamic campaign environment. It was hypothesized that voters’ information selection, processing, and recall are subject to a negativity bias (i.e., negative information dominates over positive information), a congruency bias (i.e., positive information about the preferred candidate and negative information about the opponent candidate dominate over negative information about the preferred candidate and positive information about the opponent), and a candidate bias (i.e., information about the preferred candidate dominates over information about the opponent). Motivated by an initial candidate preference, participants were also expected to develop more polarized candidate evaluations over time. Participants were exposed to quickly changing information in the form of newspaper‐style headlines on a dynamic, computer‐based information board. The results generally supported negativity bias and candidate bias, whereas congruency bias was only found during information recall. At the information selection and processing stages, participants with a strong initial candidate preference showed a disproportionate preference for negative information about the preferred candidate. However, they developed more positive attitudes at the evaluation and recall stage. This finding suggests that participants were engaged in motivated information processing by counterarguing negative information about their preferred candidate.